INTRODUCTION OF A COMMODITY TO A NEW FOREGN MARKET - O. V. Kaplina; I. A. Karachev (Финансы: теория и практика, 2017)
Modern political and economic realities force domestic companies to make a revision of their foreign-trade policies. Many producers have to change geographic directions of their businesses or the export commodity structure. In this regard, solving export marketing problems becomes a matter of strategic importance and relevance. The paper describes the purpose and the main stages of the author‘s methodology for introduction of new products to a foreign market. The investigation was performed using the methods of marketing and economic analysis. It included the study of capacity, structure and concentration of the commodity market, the analysis of entry and exit barriers, the identification of market segments as well as the simulation using the matrix method of revenues and expenses with respect to new types of export products. The implementation of the methodology is shown in the case study of the industrial rubber product market in the CIS countries for the 2010-2014 period.